Relevansi Perdebatan Liberalisme Versus Komunitarisme Untuk Konteks Indonesia - Otto Gusti Madung (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2012)
The crisis of solidarity on the one hand and political identity that denies the diversity on the other hand is a big problem that plagued the nation’s center of Indonesia. This issue is trying to read in a philosophical discourse about the glass eye kommunitarism versus liberalism. The debate between these two philosophies can be drawn mazhab its relevance to the context of Indonesia. Here, Pancasila occupies a special position.